Computer Aided Design of Molecular Imprinted Polymer for Selective Recognition of Capsaicin - Iqmal Tahir; Karna Wijaya; Shafiqul Islam; Mohd Noor Ahmad (Indonesian Journal of Chemistry, 2014)
Searching capsaicin-like molecule as an alternative dummy template has been conducted for the synthesis of Molecularly Imprinted Polymer (MIP) of capsaicin. Dummy template should be applied because synthesis of capsaicin practically has a problem due to its structure containing double bond at the aliphatic chains. Virtual searching was done using an online chemical database of ChemDB containing 5 million commercial molecules. Capsaicin structure was converted into SMILES code and then it was run on ChemDB with molecular similarity threshold of 0.5. There were 69 chemical structures obtained as the output and pseudocapsaicin was practically selected as the dummy template. Experimental result from the prediction evaluation showed that the use of capsaicin as template and pseudocapsaicin as dummy template produced MIPs that have separation factor of 1.28 and 1.25 respectively. It is suggested to choose pseudocapsaicin as dummy template for the synthesis MIP of capsaicin instead of using capsaicin molecule.